MONITORING AND EVALUATION OF EDUCATION IN IMPROVING THE QUALITY OF HIGHER EDUCATION - Hazaa, Zuhair Mubarrak; Syam, Abdi Mubarak (Academic Solution Publisher, 2025)
This study analyzes the implementation process of an internal quality assurance system (SPMI) based on the PPEPP cycle (Determination, Implementation, Evaluation, Control, and Improvement) at a newly established university, focusing on the dynamics of quality monitoring and evaluation within resource constraints. Using a descriptive qualitative approach and a case study design, this study describes the institution's adaptive strategies in building a quality culture through academic community involvement, quality system digitization, internal quality audits, and ongoing training. The results show that the success of PPEPP implementation is not solely determined by resource adequacy, but by institutional commitment, quality literacy, and data-driven participatory governance. This study provides an empirical contribution as a best practice model for new universities in preparing for accreditation and building a sustainable quality system.